THE OTHER COLOUR PATERN OF BALI CATTLE IN WEST LOMBOK REGENCY - Sudrana, I Putu; ., Lestari; Jan, Rahma; Rozy, Tapaul; Kasip, Lalu Moh. (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
The objective of this study was to identify  other colour patern of Bali cattle and the proportion  of Bali cattle that have other colour  in region of West Lombok Regency. Survey method, observation, and photography were used in the study. The study was conducted at three districts sample that divided based on high, medium, and small population of Bali cattle and also based on the condition of transportation. This study  used 31 farmers as sample.  The results  showed   that there were 10 kinds of  single other colour patern of Bali cattle, but the number of Bali cattle that had other colour patern was 11.80%.